IMPLEMENTATION OF CORPORATE CULTURE IN GOJEK MANAGEMENT - Sari, Desy Puspita; Khaerani, Reny; Refiana, Diah (Bussman Journal : Indonesian Journal of Business and Management, 2023)
Corporate culture is shared beliefs, beliefs, values and norms as a characteristic of the company and is also followed by all members of the company. Implementation becomes an activity related to the completion of a job with the use of means (tools) to obtain the results of the desired goals. This is because culture can influence organizational culture and even dictate how employees should behave in the workplace. Gojek won the MMA SMARTIES Indonesia Awards 2022. Gojek's digital advertising solution, GoPromo Ad & Discounting Tool, won an award at the 2022 MMA SMARTIES Indonesia Awards. The award was given to Gojek and WOODS' campaign which won a Gold award in the Lead Generation category. The research method used is descriptive qualitative with data collection techniques used are observation, interviews and literature study. The results of the study can be concluded that the implementation of corporate culture in managing Gojek uses three main pillars, namely speed, social impact, and innovation with the philosophy of an do attitude, how we can do differently and to be selfless